The development of social competences within university education / Dezvoltarea competențelor sociale în cadrul educației universitare - MUSIENCO Natalia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
In this article we will analyze the results obtained in our study on the development of social skills in university education. We aimed to analyze the data through the lens of the year of study and the field of education. We will also talk about social skills specific to each field of study.